Lembaga Seni Budaya Muslim Indonesia dalam Perkembangan Kesusastraan di Indonesia Tahun 1962-1966 - Samudra Eka; Dede Wiyanto (PT. Willy Print Art, 2025)
This disscouses examines how the Indonesian Muslim Cultural Arts Institute in Developing Literature in Indonesia in 1962-1966 along with the cultural divisions between various cultural institutions in Indonesia. The government's policy in responding to the literary crisis has made artists and cultural observers aggressively establish cultural institutions, differences in views between artists have made Nahdatul Ulama, which is currently modernizing culture, moved to establish the Indonesian Muslim Cultural Arts Institute (Lesbumi). The government cannot further prohibit the establishment of Lesbumi, because in its movement Lesbumi is based on divinity and humanity. Even though Lesbumi is experiencing rapid development, the core board members and members are more focused on pursuing their respective fields and making the work published by Lesbumi outnumbered when compared to other Cultural Institutions. However, Djamaluddin Malik's role as chairman of the leadership of Lesbumi had a major impact by establishing a film studio. Together with his two friends, Usmar Ismail, and Asrul Sani, Djamaluddin Malik developed Lesbumi in the film industry in Indonesia. When faced with competition from foreign films, Lesbumi through Studio Persari managed to make several high-quality films.